2020
DOI: 10.1038/s41598-020-59869-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between brain inflammatory profiles and human neuropathology are altered based on apolipoprotein E ε4 genotype

Abstract: Alzheimer disease (AD) is a chronic neurodegenerative disease with a multitude of contributing genetic factors, many of which are related to inflammation. The apolipoprotein E (APOE) ε4 allele is the most common genetic risk factor for AD and is related to a pro-inflammatory state. To test the hypothesis that microglia and AD-implicated cytokines were differentially associated with AD pathology based on the presence of APOE ε4, we examined the dorsolateral frontal cortex from deceased participants within a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Recently, Friedberg and colleagues [ 17 ] placed the above data in human context by performing post-mortem analyses on individuals from the Framingham Heart Study cohort, 35 of whom were ApoE4 carriers. Interestingly, microglial density was associated with increased tau pathology in ApoE4 carriers only, not in non-carriers.…”
Section: Microglia and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Friedberg and colleagues [ 17 ] placed the above data in human context by performing post-mortem analyses on individuals from the Framingham Heart Study cohort, 35 of whom were ApoE4 carriers. Interestingly, microglial density was associated with increased tau pathology in ApoE4 carriers only, not in non-carriers.…”
Section: Microglia and Inflammationmentioning
confidence: 99%
“…We chose to focus on these glial cells and insulin resistance because this is where the tide of recent literature on ApoE4 has turned, and sensibly so. Microglia are the resident immune cells in the brain, and it is increasingly clear that AD is an inflammatory disease [17,18]. Astrocytes are the main producers of ApoE4 in the brain as well as a primary center of cerebral lipid metabolism [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The Influence of APOE Subtype on Microglia and Tau Pathology Friedberg et al (2020) found that the density of microglia was significantly correlated with tau pathology, and the existence of tau aggregates in reactive microglia was confirmed in the brains of patients (Odawara et al, 1995;Hopp et al, 2018). In fact, PET images in mice showed that tau accumulated before the activation of microglia, and severe brain atrophy occurred after microglial activation (Ishikawa et al, 2018).…”
Section: The Influence Of Apoe Subtype On Microglia and Aβ Pathologymentioning
confidence: 97%
“…Friedberg et al [40] Cellular density of microglial marker-Iba1 was positively associated with tau pathology in APOE4 carrier participants only (n=154).…”
Section: Zhu Etmentioning
confidence: 99%